Penegakan Hukum terhadap Tindak Pidana Mengganggu Ketertiban Umum Balap Liar di Kota Bandar Lampung - Bagus Aditya indrawan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Illegal street racing is a growing social phenomenon in urban areas, conducted without official permission on public roads. This activity poses traffic accident risks and disrupts public order. From a criminal law perspective, illegal racing is considered an unlawful act under Law Number 22 of 2009 concerning Traffic and Road Transportation. This study aims to analyze the effectiveness of criminal law enforcement against illegal racing perpetrators and identify the obstacles in its implementation. The research uses a normative legal approach, utilizing secondary data such as regulations, legal literature, and court decisions. The findings reveal that law enforcement is still suboptimal due to weak supervision, lack of deterrent effects from imposed sanctions, and limited preventive and educational efforts. To address this issue, a comprehensive strategy is needed, involving coordination among law enforcement agencies, local governments, schools, and communities. Consistent legal enforcement combined with a humane and educational approach is crucial to reduce the prevalence of illegal racing and raise legal awareness among youth.